Antifriction and wear-resistant diamine benzoxazine resin as well as preparation method and application thereof
By adjusting the length of the flexible chain segment, a new bisamine benzoxazine resin was prepared, which solved the problems of high polymerization temperature and brittleness of traditional resins, achieved low polymerization temperature and excellent friction performance, and was suitable for high load and high speed working conditions.
Patent Information
- Application Number
- CN202411867139.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-12-18
AI Technical Summary
The existing bisamine benzoxazine resin has disadvantages in terms of high polymerization temperature, high brittleness, and high crosslinking density, which limits its application in friction-reducing and friction-resistant polymer matrix.
A new bisamine benzoxazine resin was prepared by using 4,4'-ethylene diphenylamine as an amine source and the length of the flexible segment was adjusted, and the resin was obtained by a hot pressing curing process.
The bisamine benzoxazine resin has low polymerization temperature, excellent thermal stability and friction properties, with a friction coefficient as low as 0.06-0.1, and a wear rate of 4.5-8.0*10-5mm3/Nm, which is suitable for high load and high speed conditions.
Smart Images

Figure CN119529209A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of thermosetting resins, and in particular relates to a friction-reducing and wear-resistant diaminobenzoxazine resin and a preparation method and application thereof. Background Art
[0002] Friction and wear are common in industrial production and daily life. Polymer materials are used as key lubricating materials for bearings, gears, hydraulic components, etc. to reduce friction and control wear due to their self-lubricating, light weight, and insulation characteristics. With the advancement of science and technology and industrial development, the service conditions of friction components are becoming increasingly harsh, causing severe challenges to the performance of these lubricating materials.
[0003] Compared with widely used phenolic resin, epoxy resin, bismaleimide and other resin matrices, benzoxazine resin, as a new type of high-performance thermosetting resin, has the advantages of low cost, excellent flame retardancy, thermal stability, low dielectric constant, relatively high carbon yield and flexible molecular design. At the same time, the heat-activated ring-opening synthesis process of benzoxazine resin can be carried out without adding any curing agent, and the curing shrinkage is almost zero. The excellent comprehensive properties of benzoxazine resin make it suitable for some molding processes such as mold pressing, lamination and resin transfer modeling. Therefore, it is used in the production of burn-resistant and corrosion-resistant materials, mechanical manufacturing parts, aerospace materials, vacuum pump vanes and other production fields. However, the development of most polymer materials is often restricted by low temperature, high cross-linking degree and high brittleness, and cannot meet some harsh environments such as high load, high speed and high temperature. As an organic polymer material, benzoxazine resin is no exception. Although traditional diaminobenzoxazine resin (PH-ddm) is a representative commercial benzoxazine resin with very wide applications in industrial production and machinery manufacturing, it has disadvantages such as high polymerization temperature, high brittleness, and high crosslinking density, which limits its use in friction-reducing and friction-resistant polymer matrices.
[0004] At present, there is no report on the research of regulating the structure of benzoxazine resin, improving its overall performance and achieving good friction reduction and wear resistance from the perspective of molecular design. Therefore, it is of great significance to design and develop benzoxazine resin materials with flexibility, good temperature resistance and excellent tribological properties by utilizing the flexibility of benzoxazine resin molecular design to broaden its application in the field of tribology. Summary of the invention
[0005] In view of some deficiencies in the prior art, the present invention provides a friction-reducing and wear-resistant bisamine benzoxazine resin and a preparation method and application thereof; the present invention uses 4,4'-ethylenediphenylamine as an amine source and prepares a bisamine benzoxazine resin by adjusting the length of the flexible segment; the bisamine benzoxazine resin has excellent thermal stability and friction performance, a friction coefficient as low as 0.06-0.1, and a wear rate of 4.5-8.0*10-5 mm 3 / Nm, and still maintains good friction reduction and wear resistance under high load and high speed; the bisamine benzoxazine resin has a low polymerization temperature and very excellent thermal, mechanical and friction properties; the preparation method of the bisamine benzoxazine resin is simple, the yield is high, the equipment requirements are low, it is easy to achieve large-scale production, and it has good practicality.
[0006] In order to achieve the above technical objectives, the present invention adopts the following technical means:
[0007] The present invention first provides a friction-reducing and wear-resistant bisamine benzoxazine resin, wherein the molecular chemical structure of the bisamine benzoxazine resin is:
[0008]
[0009] in, Any one of (A) to (E):
[0010]
[0011] The present invention also provides a method for preparing the above-mentioned bisamine benzoxazine resin, the preparation method comprising:
[0012] 4,4'-ethylenediphenylamine, phenolic compounds and paraformaldehyde are mixed, and then a low-polarity solvent is added thereto, and the mixture is evenly mixed and then heated for reaction. After the reaction is completed, the mixture is filtered, washed, rotary evaporated and dried to obtain a solid product, i.e., a bisamine benzoxazine monomer; and then the bisamine benzoxazine monomer is hot-pressed and cured to obtain a bisamine benzoxazine resin.
[0013] Preferably, the phenolic compound has the structural formula Including any one of A to E:
[0014]
[0015] Preferably, the molar ratio of 4,4'-ethylenediphenylamine, the phenolic compound and paraformaldehyde is 1:2:4 to 1:2:6.
[0016] Preferably, the molar ratio of 4,4'-ethylenediphenylamine, phenolic compound and paraformaldehyde is 1:2:4.4.
[0017] Preferably, the low polarity solvent includes one or a mixture of toluene, xylene, and dioxane.
[0018] Preferably, the heating reaction is carried out at 80-130° C. for 6-8 hours.
[0019] Preferably, the conditions for the hot pressing curing are: pressing at 180-240° C. and a pressure of 3-7 MPa for 8-10 hours.
[0020] The present invention also provides the use of the above-mentioned diaminobenzoxazine resin in the field of friction reduction and wear resistance.
[0021] Preferably, the application includes: production of transmission / moving parts of sliding bearings or high-temperature bushings under heavy-load and high-speed conditions. Compared with the prior art, the beneficial effects of the present invention are:
[0022] The present invention uses 4,4'-ethylene diphenylamine as an amine source to synthesize a novel diaminobenzoxazine monomer containing a flexible segment, and then heat-presses and solidifies the diaminobenzoxazine monomer to obtain the diaminobenzoxazine resin. Compared with the traditional commercial diaminobenzoxazine resin (PH-ddm), the diaminobenzoxazine resin of the present invention has elongated flexible bridge chains between benzene rings, so that the fluidity of the polymer chain is enhanced, thereby improving the thermal stability and tribological properties of the resin.
[0023] The diaminobenzoxazine resin of the present invention has better thermal stability and lower polymerization temperature than the traditional benzoxazine resin, and its friction coefficient is as low as 0.06-0.1, and the wear rate is 4.5-8.0*10 -5 mm 3 / Nm, and still maintains good friction reduction and wear resistance under high load and high speed. The friction coefficient of traditional commercial bisamine benzoxazine resin (PH-ddm) is 0.35, and the wear rate is 8.5*10 -4 mm 3 / Nm. In contrast, the bisaminobenzoxazine resin of the present invention exhibits excellent friction reduction and wear resistance, which provides the necessary conditions for it to be used as a polymer lubricating material.
[0024] The bisamine benzoxazine resin of the present invention has a simple synthesis process, a high yield (about 88%), low requirements on equipment, and is suitable for large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the diaminobenzoxazine monomer.
[0026] Figure 2 This is the infrared spectrum of the diaminobenzoxazine monomer.
[0027] Figure 3 This is the DSC spectrum of the diaminobenzoxazine monomer.
[0028] Figure 4 This is the TGA spectrum of bisamine benzoxazine resin.
[0029] Figure 5 This is a graph showing the coefficient of friction of bisamine benzoxazine resin.
[0030] Figure 6 Figure 2 is a graph showing the friction coefficient and wear rate of bisamine benzoxazine resin. DETAILED DESCRIPTION
[0031] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments, but the protection scope of the present invention is not limited thereto.
[0032] The reaction equation of the reaction of the present invention is:
[0033]
[0034] Wherein, the phenolic compound structural formula is It includes any one of A to E:
[0035]
[0036] Example 1: Preparation of bisamine benzoxazine resin
[0037] In this example, 4,4'-ethylenediphenylamine was used as an amine source and phenol was used as a phenol source to prepare a bisamine benzoxazine resin. The structural formula of the bisamine benzoxazine resin is:
[0038]
[0039] The equation for the reaction is:
[0040]
[0041] The specific preparation steps are as follows:
[0042] 1.06 g (0.005 mol) of 4,4'-ethylenediphenylamine, 0.94 g (0.010 mol) of phenol and 0.622 g (0.022 mol) of polyformaldehyde were added to a 100 mL round-bottom flask and mixed. Then, 50 mL of toluene solution was added thereto. A condenser was connected and the mixture was stirred at 120°C for 6 h. After the reaction was completed, the mixture was cooled to room temperature and the solvent was removed by rotary evaporation to obtain a crude product. The bisaminobenzoxazine monomer was then recrystallized from ethanol with a yield of 88%.
[0043] The bisaminobenzoxazine monomer was subjected to hot pressing curing under the conditions of pressing at 180° C. and a pressure of 5 MPa for 9 hours to obtain a bisaminobenzoxazine resin.
[0044] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the diaminobenzoxazine monomer. It can be seen from the figure that the chemical shifts around 5.4ppm and 4.6ppm are the characteristic peaks of the oxazine ring. Figure 2This is the infrared spectrum of the diaminobenzoxazine monomer. It can be seen from the figure that 945 and 1229 cm -1 The characteristic absorption peak of benzoxazine ring is at Figure 1 and 2 It can be seen that the diaminobenzoxazine monomer was successfully synthesized in this example.
[0045] Figure 3 : is the DSC spectrum of the bisamine benzoxazine monomer. It can be seen from the figure that the curing exothermic peak temperature of the benzoxazine monomer is 227.5° C., which indicates that the bisamine benzoxazine resin prepared by the present invention has a lower polymerization temperature.
[0046] Figure 4 3 is the TGA spectrum of the bisamine benzoxazine resin. It can be seen from the figure that the temperature at which the benzoxazine resin loses 10% of its thermal weight is 392°C, and the carbon residue rate at 800°C is 51%, which indicates that the bisamine benzoxazine resin prepared by the present invention has high thermal stability.
[0047] Figure 5 This is the friction coefficient diagram of the bisamine benzoxazine resin. It can be seen from the figure that the average friction coefficient of the benzoxazine resin in the stable stage is as low as 0.06.
[0048] Figure 6 The friction coefficient and wear rate of the diamine benzoxazine resin are shown in the figure. It can be seen from the figure that the wear rate of the benzoxazine resin is 4.5×10 -5 mm 3 / Nm. The friction coefficient of commercial diaminobenzoxazine resin PH-ddm is 0.35 and the wear rate is 8.5*10 -4 mm 3 / Nm. In contrast, the bisaminobenzoxazine resin of the present invention exhibits excellent friction reduction and wear resistance, and its wear rate is reduced by one order of magnitude compared with the commercialized bisaminobenzoxazine, which provides the necessary conditions for it to be used as a polymer lubricating material.
[0049] Example 2: Preparation of bisamine benzoxazine resin
[0050] In this example, 4,4'-ethylenediphenylamine was used as an amine source and 4-chlorophenol was used as a phenol source to prepare a bisamine benzoxazine resin. The structural formula of the bisamine benzoxazine resin is:
[0051]
[0052] The specific preparation steps are as follows:
[0053] 1.06 g (0.005 mol) of 4,4'-ethylenediphenylamine, 1.29 g (0.010 mol) of 4-chlorophenol and 0.60 g (0.020 mol) of polyformaldehyde were added to a 100 ml round-bottom flask and mixed. Then, 50 ml of toluene solution was added thereto. A condenser was connected and the mixture was stirred at 130°C for 6 h. After the reaction was completed, the mixture was cooled to room temperature and the solvent was removed by rotary evaporation to obtain a crude product. The bisaminobenzoxazine monomer was then recrystallized from ethanol with a yield of 88%.
[0054] The bisaminobenzoxazine monomer was hot-pressed and cured at 240° C. and a pressure of 3 MPa for 8 h to obtain a bisaminobenzoxazine resin.
[0055] The bisamine benzoxazine monomer is cured by hot pressing to obtain a bisamine benzoxazine resin.
[0056] The test shows that the curing exothermic peak temperature of the bisamine benzoxazine monomer prepared in this embodiment is 230.4°C. The temperature of the bisamine benzoxazine resin after further curing and cross-linking is 394°C when the thermal weight loss is 10%. When the inert gas atmosphere is 800°C, the carbon residue rate is 54%, the friction coefficient is 0.096, and the wear rate is 6.9×10 -5 mm 3 / Nm.
[0057] Example 3: Preparation of bisamine benzoxazine resin
[0058] In this example, 4,4'-ethylenediphenylamine was used as an amine source and 4-methylphenol was used as a phenol source to prepare a bisamine benzoxazine resin. The structural formula of the bisamine benzoxazine resin is:
[0059]
[0060] The specific preparation steps are as follows:
[0061] 1.06 g (0.005 mol) of 4,4'-ethylenediphenylamine, 1.08 g (0.010 mol) of 4-methylphenol and 0.75 g (0.025 mol) of polyformaldehyde were added to a 100 ml round-bottom flask and mixed, and then 50 ml of toluene solution was added thereto, and a condenser was connected. The mixture was stirred and reacted at 100 ° C for 7 hours. After the reaction was completed, it was cooled to room temperature, and the solvent was removed by rotary evaporation to obtain a crude product, which was then recrystallized from ethanol to obtain a bisaminobenzoxazine monomer with a yield of 85%.
[0062] The bisaminobenzoxazine monomer was hot-pressed and cured at 200° C. and a pressure of 5 MPa for 9 hours to obtain a bisaminobenzoxazine resin.
[0063] The test shows that the peak temperature of the curing exothermic reaction of the bisamine benzoxazine monomer prepared in this embodiment is 232.8°C. The temperature of the bisamine benzoxazine resin after further curing and cross-linking is 397°C when the thermal weight loss is 10%. When the inert gas atmosphere is 800°C, the carbon residue rate is 56%, the friction coefficient is 0.08, and the wear rate is 7.2×10 -5 mm 3 / Nm.
[0064] Example 4: Preparation of bisamine benzoxazine resin
[0065] In this example, 4,4'-ethylenediphenylamine was used as an amine source and 4-fluorophenol was used as a phenol source to prepare a bisamine benzoxazine resin. The structural formula of the bisamine benzoxazine resin is:
[0066]
[0067] The specific preparation steps are as follows:
[0068] 1.06 g (0.005 mol) of 4,4'-ethylenediphenylamine, 1.12 g (0.010 mol) of 4-fluorophenol and 0.84 g (0.028 mol) of polyformaldehyde were added to a 100 ml round-bottom flask and mixed. Then, 50 ml of toluene solution was added thereto. A condenser was connected and the mixture was stirred at 90°C for 8 h. After the reaction was completed, the mixture was cooled to room temperature and the solvent was removed by rotary evaporation to obtain a crude product. The bisaminobenzoxazine monomer was then recrystallized from ethanol with a yield of 86%.
[0069] The bisaminobenzoxazine monomer was hot-pressed and cured at 190° C. and a pressure of 6 MPa for 9 h to obtain a bisaminobenzoxazine resin.
[0070] The test shows that the curing exothermic peak temperature of the bisamine benzoxazine monomer prepared in this embodiment is 235.8°C. The temperature of the bisamine benzoxazine resin after further curing and cross-linking is 403°C when the thermal weight loss is 10%. When the inert gas atmosphere is 800°C, the carbon residue rate is 58%, the friction coefficient is 0.07, and the wear rate is 6.3×10 -5 mm 3 / Nm.
[0071] Example 5: Preparation of bisamine benzoxazine resin
[0072] In this example, 4,4'-ethylenediphenylamine was used as an amine source and 4-cyanophenol was used as a phenol source to prepare a bisamine benzoxazine resin. The structural formula of the bisamine benzoxazine resin is:
[0073]
[0074] The specific preparation steps are as follows:
[0075] 1.06 g (0.005 mol) of 4,4'-ethylenediphenylamine, 1.19 g (0.010 mol) of 4-cyanophenol and 0.90 g (0.030 mol) of paraformaldehyde were added to a 100 ml round-bottom flask and mixed, and then 50 ml of toluene solution was added thereto, and a condenser was connected. The mixture was stirred and reacted at 80°C for 8 hours. After the reaction was completed, it was cooled to room temperature, and the solvent was removed by rotary evaporation to obtain a crude product, which was then recrystallized from ethanol to obtain a bisaminobenzoxazine monomer with a yield of 88%.
[0076] The bisaminobenzoxazine monomer was hot-pressed and cured at 180° C. and a pressure of 7 MPa for 10 h to obtain a bisaminobenzoxazine resin.
[0077] The test shows that the curing exothermic peak temperature of the bisamine benzoxazine monomer prepared in this embodiment is 236.8°C. The temperature of the bisamine benzoxazine resin after further curing and cross-linking is 406°C when the thermal weight loss is 10%. When the inert gas atmosphere is 800°C, the carbon residue rate is 59%, the friction coefficient is 0.1, and the wear rate is 8.0×10 -5 mm 3 / Nm.
[0078] In summary, the present invention uses 4,4'-ethylenediphenylamine as an amine source and prepares a diaminobenzoxazine resin by adjusting the length of the flexible segment; the diaminobenzoxazine resin has excellent thermal stability and friction performance, a friction coefficient as low as 0.06-0.1, and a wear rate of 4.5-8.0*10 -5 mm 3 / Nm, and still maintains good friction reduction and wear resistance under high load and high speed; the bisamine benzoxazine resin has a low polymerization temperature and very excellent thermal, mechanical and friction properties; the preparation method of the bisamine benzoxazine resin is simple, the yield is high, the equipment requirements are low, it is easy to achieve large-scale production, and it has good practicality.
[0079] The embodiments are preferred implementations of the present invention, but the present invention is not limited to the above-mentioned implementations. Any obvious improvements, substitutions or modifications that can be made by those skilled in the art without departing from the essential content of the present invention belong to the protection scope of the present invention.
Claims
1. A friction-reducing and wear-resistant diaminobenzoxazine resin, characterized in that: The molecular chemical formula of the bisamine benzoxazine resin is: in, Any one of (A) to (E):
2. The method for preparing the bisamine benzoxazine resin according to claim 1, characterized in that: The preparation method comprises: 4,4'-ethylenediphenylamine, phenolic compounds and paraformaldehyde are mixed, and then a low-polarity solvent is added thereto, and the mixture is evenly mixed and then heated for reaction. After the reaction is completed, the mixture is filtered, washed, rotary evaporated and dried to obtain a solid product, i.e., a bisamine benzoxazine monomer; and then the bisamine benzoxazine monomer is hot-pressed and cured to obtain a bisamine benzoxazine resin.
3. The method for preparing the bisamine benzoxazine resin according to claim 2, characterized in that: The phenolic compound structural formula is Including any one of A to E:
4. The method for preparing the bisamine benzoxazine resin according to claim 2, characterized in that: The molar ratio of 4,4'-ethylenediphenylamine, phenolic compound and paraformaldehyde is 1:2:4 to 1:2:
6.
5. The method for preparing the bisamine benzoxazine resin according to claim 4, characterized in that: The molar ratio of 4,4'-ethylenediphenylamine, phenolic compound and paraformaldehyde is 1:2:4.
4.
6. The method for preparing the bisamine benzoxazine resin according to claim 2, characterized in that: The low polarity solvent includes one of toluene, xylene, and dioxane, or a mixture of several of them.
7. The method for preparing the bisamine benzoxazine resin according to claim 2, characterized in that: The heating reaction conditions are: reacting at 80-130° C. for 6-8 hours.
8. The method for preparing the bisamine benzoxazine resin according to claim 2, characterized in that: The conditions for the hot pressing curing are: pressing at 180-240° C. and a pressure of 3-7 MPa for 8-10 hours.
9. Use of the bisamine benzoxazine resin according to claim 1 in the field of friction reduction and wear resistance.
10. The use according to claim 9, characterized in that: The applications include the production of transmission / movement parts such as plain bearings or high-temperature bushings for heavy-duty and high-speed applications.
Citation Information
Patent Citations
Binder resin for friction material, binder resin, and method for manufacturing the same
JP2009132753A
Composition for resist underlayer film formation, resist underlayer film and method for forming the same, and production method of a patterned substrate
US20190212650A1